UI/UX Redesign of INHIL Dukcapil Application Using the Design Thinking Method - Rosi Yulia; Reski Mai Candra; Muhammad Irsyad; Teddie Darmizal (INFOKUM, 2022)
The population and civil registration office is an agency directly related to the city government that is tasked with providing population registration services and civil registration services. Now technological advances are helping to modernize public services, including population administration services in Riau Province. There are 3 districts that have implemented services using smartphone applications. One of them is Indragiri Hilir Regency with the name Dukcapil Inhil Application. The Dukcapil Inhil application was released to make it easier for people to take care of population administration. However, in its use there are several problems. This research was conducted to develop application recommendations by analyzing and redesigning the UI and UX of the Dukcapil Inhil Application using the Design Thinking method. This method is used to take a solution-based approach that will be used for problem solving, by understanding application users to define existing problems and then make a solution to solve existing problems. Application recommendations are built in the form of prototypes using the Figma application. The prototype built was successfully tested on 10 respondents using System Usability Scale (SUS) testing and the application prototype was rated 78.